The Effect of Mental Workload on the Prevalence of Musculoskeletal Disorders (Case Study: Bandar Abbas Zinc Production Company) - Hadi SALARI; Mohammad Reza GHOTBI-RAVANDIR; Mohammad DASTANPOUR; Sajad ZARE (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Introduction: One of the effective factors in the occurrence of musculoskeletal disorders is the mismatch between the mental workload on the person and his abilities and limitations. Therefore, this study aimed to investigate the effect of mental workload on the prevalence of musculoskeletal disorders in Bandar Abbas Production Company. Method: This cross-sectional descriptive-analytical study was conducted in 2019. The data collection tools included demographic information questionnaires, Nordic musculoskeletal disorders, and NASA- TLX mental workload. The participants were 172 people who were identified using Cochran's formula and simple random sampling. The collected data were analyzed by SPSS 25 software. Results: The results indicated that 76.74% of the subjects had musculoskeletal disorders. Most of disorders were reported in the low back (51.16%), knees (38.95%), and neck (23.84%). The mean score of mental workloads in Bandar Abbas Production Company in this study was high (66.67). Among the mental workload subscales, the effort subscale had the highest score (85.32) and the performance subscale had the lowest score (20.00). Statistical tests showed that there was a significant relationship between mental workload and the prevalence of musculoskeletal disorders. Conclusion: According to the findings of the study, there was a direct relationship between mental workload and the prevalence of musculoskeletal disorders. Therefore, measures should be taken to reduce the perceived mental and psychological load, such as reducing working hours, interrupting and resting between working, increasing the variety of working postures, and thus preventing the occurrence of musculoskeletal disorders.